Operation of an industrial electron accelerator in a double-beam e,X-mode - Shevchenko, V.A.; Tenishev, A.Eh.; Uvarov, V.L.; Zakharchenko, A.A. (Вопросы атомной науки и техники, 2019)
Analysis of mixed e,X-radiation formation in output devices of an industrial electron accelerator is conducted. The possibility is demonstrated to obtain an extra radiation channel on the basis of a practically free source of Xrays simultaneously with the main channel of product processing with electron beam. The conditions of production of the secondary radiation in the state of electronic equilibrium at product treatment with scanning electron beam in the main radiation channel are studied by means of computer simulation. The dependence of spatial radiant characteristics of the X-ray radiation on the spectrum of a primary electron beam and surface density of a treated load has been established. For an industrial accelerator LU-10 of NSC KIPT, the regime of object processing in the extra radiation channel is examined. The results of calculation of the X-ray dose rate and its spatial distribution are in good agreement with the experimental data. The comparative capacity of both radiation channels of the plant is analyzed. The extra radiation source can be used for the execution of non-commercial programs like sanitation of cultural artefacts.